2020
DOI: 10.1093/gigascience/giaa114
|View full text |Cite
|
Sign up to set email alerts
|

Pacific Biosciences assembly with Hi-C mapping generates an improved, chromosome-level goose genome

Abstract: Background The domestic goose is an economically important and scientifically valuable waterfowl; however, a lack of high-quality genomic data has hindered research concerning its genome, genetics, and breeding. As domestic geese breeds derive from both the swan goose (Anser cygnoides) and the graylag goose (Anser anser), we selected a female Tianfu goose for genome sequencing. We generated a chromosome-level goose genome assembly by adopting a hybrid de novo assembly approach that combined P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…We also used all three published geese genomes and 12 other chromosome-level bird genomes to carry out BUSCO 19 analyses to delve into the completeness of the XGG genome. The results showed that 95.7% of complete genes and 1.0% of fragments of genes were identified from the 8,338 core genes in the Aves dataset, better than the evaluation results of TFG 3 (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…We also used all three published geese genomes and 12 other chromosome-level bird genomes to carry out BUSCO 19 analyses to delve into the completeness of the XGG genome. The results showed that 95.7% of complete genes and 1.0% of fragments of genes were identified from the 8,338 core genes in the Aves dataset, better than the evaluation results of TFG 3 (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 67%
“…To further assess the accuracy of the scaffolded genome, we realigned the Illumina paired-end reads to the XGG genome with high mapping (99.19%) and high coverage rates (97.96%), generally reflecting the base accuracy of the reliable genome (Supplementary Table 6 ). The genome was further evaluated by CEGMA 18 , and 92.3% of 248 core genes from six eukaryotic model organisms could be identified (Supplementary Table 7 ), a value that was significantly higher than the evaluation results (85.08%) of TFG 3 . We also used all three published geese genomes and 12 other chromosome-level bird genomes to carry out BUSCO 19 analyses to delve into the completeness of the XGG genome.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…After removing the adaptors, the sequences with uncertain bases, low-quality sequences, and sequences of less than 50 bp, as well as the high-quality data from the 45 libraries were mapped to the goose genome, which was assembled by our lab ( Li et al, 2020 ) by alignment tool STAR (version 2.6.0c) ( Dobin and Gingeras, 2015 ; Dobin and Gingeras, 2016 ) with the parameters of ENCODE standard RNA-seq pipeline. Then, the transcripts were reconstructed with parameters of -g -u -b --library-type fr-first strand using the Cufflinks (2.2.1) ( Pollier et al, 2013 ; Ghosh and Chan, 2016 ).…”
Section: Methodsmentioning
confidence: 99%